Investigation of the evolution of deformation field and crack propagation characteristics of sandstone containing an arched roadway - Yan, Yao; Zhang, Yuqi; Zhou, Meiling (Frontiers in Earth Science, 2025)
In mining, tunneling, and other engineering activities, the stability and strength of the surrounding rock system are primarily governed by the dynamic evolution of crack initiation, propagation, and interconnection in the rock material. To investigate the fracture process of sandstone containing an arched roadway under uniaxial compression, yellow sandstone samples with arched roadways were prepared, and their displacement field, strain field evolution, and crack propagation characteristics were revealed using digital image correlation (DIC) technology. The results show that under uniaxial loading, the deformation and failure process of yellow sandstone samples containing arched roadways can be divided into four stages: initial compaction, elastic deformation, plastic deformation, and instability failure, with the peak stress measured at approximately 16 MPa. As the load increases, the displacement and strain fields evolve, and their values gradually increase. Before the load level reaches 70%, the displacement and strain values increase slightly, reaching approximately 0.3 mm and 0.01, respectively. During the accelerated crack growth stage, the displacement and strain values increase rapidly. At 100% load, the maximum displacement and strain values reach 0.4 mm and 0.03, respectively. After brittle failure, the instantaneous displacement and strain can increase to 1 mm and 0.06, respectively. During the loading process, the maximum principal strain of each crack around the arched roadway increases and evolves asynchronously. The strain distribution on the left and right sides of the roadway is significantly greater than that on the upper and lower sides, exhibiting a degree of symmetry. By analyzing the included angle of crack initiation and the horizontal and vertical displacement values at two points on either side of the crack initiation position, the relative displacement in the tangential and normal directions of each crack can be determined. Combined with difference calculations, the tensile and shear properties of the crack, along with the corresponding initiation time and stress, can be quantified. Under uniaxial loading, the cracks in the yellow sandstone samples with arched roadways are predominantly mode I cracks. These research findings provide valuable insights to advance understanding of the mechanical response and crack propagation evolution of surrounding rock in roadway engineering.